COMMUNICATIVE AND COGNITIVE CONTROL CONCEPT GEOENVIRONMENTAL RESOURCES OF THE REGION - BARBARA RAFAELOVNA Markarian (Мир новой экономики)
Changes in the external macroeconomic conditions in which the regions of Russia are at the moment require the development of new approaches to their development management. Therefore for developing Programs for regional development the main task of the leaders of the domestic economy should be in chasing the high economic indicators not to forget about the other no less important, especially in the border regions, priorities of the state, such as social stability and ethnic harmony.In article the author proves that when developing regional strategy in constantly changing environment, it is necessary to consider the basic principles of advance communicative planning which treat, first of all,the accounting of demographic and ethnic structure of the population, its ethical and historical values, i.e. geoethnoeconomic capacity of the region.The article shows the methods and tools of involving geo-ethno-economic resources of the region, namely ethno economic factors in the regional socio-economic systems development.